Bunny cakes - Wells, Rosemary (Dial Books for Young Readers, 1997)
Max makes an earthworm cake for Grandma's birthday and help Ruby with her angel surprise cake. At the store, the grocer can't read all of the shopping list, until Max solves the problem by drawing a picture.